Odpowiedzi

2010-03-31T20:44:13+02:00
ODP:
a i e są takie same, tylko literki są inne

b) 2(2x – 3) (x + 1) – 5(x-1)² = 2(x-2)(x-1)
c) -x² - 3x + 4 ≥ 0
Δ=b²-4ac=(-3)²-4x(-1)x4=9+16=25
√Δ=√25=5
x1= -b- √Δ/2a=3-5/2x(-1)= -2/-2= 1
x2= -b+√Δ/2a=3+5/2x(-1)= 8/-2= -4

d) x² -7x + 12 > 0
Δ=b²-4ac= (-7)² - 4×1×12=49-48=1
x1= -b- √Δ/2a= 7-1/2×1= 6/2=3
x2= -b+ √Δ/2a= 7+1/2x1=8/2=4

e) -4a² - 16a +9 < 0
Δ=b²-4ac= (-16)² -4×(-4)×9=256+144=400
√Δ=√400=√100x4= √10√4=20√2
x1= -b- √Δ/2a=16-20√2/2x(-4)=16-20√2/-8=2-20√2
x2= -b+√Δ/2a=16+20√2/2x(-4)=16+20√2/-8=2+20√2


f) x² -6x + 9 ≤ 0
Δ=b²-4ac=(-6)² -4x1x9=36-36=0
x0= -b/2a=6/2x1= 6/2=3